Kvantitativna fluorescenčna verižna reakcija s polimerazo (QF-PCR) kot alternativni test za hitro prenatalno genetsko testiranje - Erjavec Škerget, Alenka (Anali PAZU, 2011)
Diagnosis of common chromosome aneuploidies have been successful through quantitative fluorescent PCR (QF-PCR) assays and small tandem repeats (STR) markers. Our objective was to present and to analyze the results of the first three years of a QF-PCR testing strategy for the prenatal diagnosis of common chromosome aneuploidy (trisomy of chromosome 21, 18 and 13) and to discuss about the advantages and disadvantages of methodology. Amniotic fluid or chorionic villus samples were collected from mother undergoing prenatal invasive testing for fetal abnormalities on ultrasonic examination or abnormal maternal serum aneuploidy screening results. Rapid diagnoses were performed using QF-PCR analysis with several STRs markers specific for chromosomes 13, 18, 21, Y and amelogenin X/Y alleles. One QF-PCR testing consisted of six multiplexes reactions. Of the 243 samples received (amniotic cells 72.3 %, chorionic villi 27.2 %, placentocentesis 0.5 %) 7.8 % had a chromosome abnormality detected by QF-PCR testing. All cases with numerical chromosome abberations involving chromosomes 21, 18, 13 were correctly diagnosed (100 %). Of 66 samples 4.5 % of samples received a normal QF-PCR result but subsequently had an abnormal karyotype because the present QF-PCR assay was not designed to detect them. Of these samples only 1/3 had a chromosome abnormality associated with a poor prognosis. Based on our result the sensitivity of the QF-PCR assay was 95.4 %, the specificity 100 % and the efficiency 98.8 %, respectively. Our study demonstrates that QF-PCR is a reliable technique that aids clinical management of pregnancy as rapid method for the detection of common numerical chromosome disorders by woman at high risk for fetal aneuploidy. While karyotyping is still required for all samples in Slovenia, using QF-PCR as a stand-alone prenatal test for pregnancies without ultrasound abnormalities reduces costs, provides rapid delivery of results, and avoids ambiguous and uncertain karyotype results, reducing parental anxiety.
Keywords: fluorescenčna verižna reakcija; genetika; kromosomske anevplodije; polimeraza; prenatalno testiranje